The nature and content of rumination for head and neck cancer survivors - Menger, Fiona; Deane, Jennifer; Patterson, Joanne M.; Fisher, Peter; O’Hara, James; Sharp, Linda (Frontiers in Psychology, 2022)
Introduction Head and neck cancer (HNC) diagnosis and treatment can be a significant life trauma. Some HNC survivors experience post-traumatic growth (PTG), which has been linked with better health-related quality-of-life. Empirical research on PTG, and theoretical models, point to the importance of being able to purposely make sense of the traumatic experience. Intrusive rumination, by contrast, is linked to poorer outcomes. This study explored HNC survivors’ experiences of rumination. Methods Twenty HNC survivors between nine months and five years post-diagnosis were recruited (11 male, 9 female, age range 46-83). They had a range of HNC sub-types and cancer treatments. Participants underwent a semi-structured interview about their cancer diagnosis and treatment. Reflexive thematic analysis identified themes and sub-themes around rumination. Results Four themes with linked subthemes on the content and process of rumination were identified. Theme 1 was rumination and worry related to diagnosis. Here, survivors discussed how the HNC diagnosis and plans for treatment had dominated their initial thoughts. Theme 2 was processing the trauma of HNC. This theme reflected rumination on the traumatic experience of diagnosis and treatment and how the participant was reacting to it. Theme 3 was considering the impact. This theme encompassed retrospective thinking (e.g., on treatment decisions made) and comparisons between the participant now versus the early days after diagnosis. Theme 4 was continued rumination. This theme included ongoing intrusive and distressing rumination about the trauma and impact of cancer. Those who expressed ongoing rumination revisited fears (e.g., concerns about their future) or returned to negative experiences (e.g., distressing exchanges with healthcare professionals or what they perceived as poor care). Conclusions This study uniquely describes the nature and content of rumination following HNC. Early intrusive rumination is common and may reflect perceptions of cancer as an existential threat. Over time, rumination can become more reflective and move towards deliberate meaning-making. Some HNC survivors may benefit from interventions to reduce barriers to this transition. The content of distressing and difficult to control rumination (commonly focused on ongoing fears or inability to resolve difficult experiences) helps to identify those who may benefit from more directed psychological support.